1986
DOI: 10.1271/bbb1961.50.2853
|View full text |Cite
|
Sign up to set email alerts
|

Okadaic acid as the causative toxin of diarrhetic shellfish poisoning in Europe.

Abstract: The toxic principle in mussels collected in France, Sweden, the Netherlands, and Spain that caused diarrhetic shellfish poisoning was identified to be okadaic acid by its chromatographic properties and spectral data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
19
0

Year Published

1987
1987
2009
2009

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(19 citation statements)
references
References 1 publication
0
19
0
Order By: Relevance
“…Okadaic acid was also found in European mussels as the toxic principle of a seafood disease (Kumagai et al, 1986).…”
mentioning
confidence: 91%
“…Okadaic acid was also found in European mussels as the toxic principle of a seafood disease (Kumagai et al, 1986).…”
mentioning
confidence: 91%
“…Phone: +44 28 9097 6562. toxin varies in each occurrence and usually includes complex mixtures of toxins. OA is found worldwide but is reported to be the dominant OA-group toxin in Europe, 16 whereas outbreaks of DSP in Japan have mainly been associated with DTX-1. 17 DTX-2 has been reported in shellfish from Spain, Portugal, and Norway, 18 and in Ireland there are reports of higher levels of DTX-2 than OA.…”
mentioning
confidence: 99%
“…OA accumulates in the hepatopancreas of bivalves (Murakami et al, 1982;Kumagai et al, 1986) that are also potentially cocontaminated by environmental pollutants such as heavy metals (including Mercury, Cadmium, and Chromium). OA is known to be a potent inhibitor of serine/ threonine phosphatases (Bagu et al, 1997;Biolojan and Takai, 1998) and a specific inhibitor of protein synthesis through hyperphosphorylation of elongation factor EF2 (Matias et al, 1996(Matias et al, , 1999a.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that OA is widely distributed in mammals after consumption (Matias et al, 1999b), the main effects being in the intestinal tract where it is responsible for DSP (Kumagai et al, 1986;Sueoka and Fujiki, 1997).…”
Section: Introductionmentioning
confidence: 99%